Analysis of the Effect of Adaptive Competence Customer relation officer on Service recovery Performance - Ayu Adriana Putri; Rachma Fitriati (Universitas Medan Area, 2020)
The purpose of this study was to analyze the effect of the adaptive ability of customer relation officers in service recovery performance in the One Stop Integrated Services and Investment Office of the Special Capital Region of Jakarta (DKI). The method used in this research is quantitative. Sources of data were taken from informants, namely customer relation officers who were directly involved in the recommendation service for Building Use Rights over Land Management Rights, namely 50 respondents. The data collection technique was carried out by conducting initial interviews and distributing and filling out questionnaires. The results of the study found that culture competence, self management, social capacity, self-efficacy recovery and organizational system recovery, affect service recovery performance while informational fairness has no effect on service recovery performance of customer relation officers.